In a sea of crumbling icebergs - Dieter Wolf-Gladrow; Ines Borrione; Gayatri Shirodkar; Mangesh U. Gauns; Murty Vadlaman; Christine Klaas (Journal of Glaciology, 2025)
In January 2009, on its way from Cape Town to South America (at around 49.5∘S and 25∘W), the German research vessel Polarstern entered a region with a dense cover of icebergs and broken-off chunks of ice up to a few meters in size, largely hidden in a thick fog, a result of the microclimate created by the large agglomeration of icebergs and broken-off glacial ice. Melting of glacial ice led to a cooling (by up to 8∘C) and freshening (by up to 2.5 psu) of the surface ocean with perturbations reaching down to about 75 m depth. The observed surface ocean equilibrium fugacity of CO2, fCO2, dropped to values that were over 100 µatm lower than atmospheric fCO2 values. Given the similar concentrations in chlorophyll a and the macronutrients nitrate and phosphate inside and outside the perturbed areas, influences of potential iron input from disintegrating icebergs on phytoplankton productivity and fCO2 can be ruled out. The low fCO2 values, compared to adjacent regions, can be attributed to thermodynamic effects, i.e. mostly increase of CO2 solubility with decreasing temperature with a smaller contribution from the dilution due to freshwater inputs. Based on these observations, we consider the potential impact on atmospheric fCO2 by the release of an armada of icebergs during Heinrich events.